ТУРЛИ БИЛИМ СОҲАЛАРИГА НИСБАТАН КОМПЕТЕНЦИЯНИ ШАКЛЛАНТИРИШ МОДЕЛЛАРИНИ ЯРАТИШ МЕТОДОЛОГИЯСИ - Агжанов, Т. (SCIENCE and SOCIETY, 2024)
The article examines the methodological issues of creating a model of educational publications that help to ensure appropriate relations between society and people with information culture. Taking into account the characteristics and indicators of the industry with the features of the information culture of the society, which is important for the activity of this field, it considers the structure of the activity on various bases of this activity, taking into account the current situation.